La pena de muerte legitimada en el derecho comparado y su incidencia en la disminución de delitos - Villarreal Paguay, Kevin Alexander (2024)
ABSTRACT: The present investigation work focuses on the analysis of the death penalty legitimized in comparative law and its impact on the reduction of crimes, taking as a fundamental basis all the legislations in which, if said sanction is in force, as well as those that are not, this will allow us to know if there is a difference between some and others in relation to the crime rate and the commission of crimes. The research will have a survey in which it will help us determine the thought and point of view that the recipients of said questionnaire have, about the death penalty and whether or not this can be a factor in reducing crimes is aimed especially at 75 citizens between 30 and 70 years of age, free-lance lawyers practicing, members of the clergy and psychology professionals. The result that was evident throughout the investigation is that without a doubt, the penalty of Death is a topic that always raises a debate about whether it is right to apply it or not, but without a doubt It was shown that in the majority of cases in which this sanction is in force it does not influence a factor in the commission of crimes, but in a certain way it does help to have control on society and that currently, some countries where the death penalty has been abolished death and that, due to existing crime, citizens request and are in favor of that said sanction be implemented in their legislation.